1999
DOI: 10.1093/occmed/49.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Health surveillance in milling, baking and other food manufacturing operation—five years' experience

Abstract: The objective of this study was to describe the incidence of allergic respiratory disease and its outcome in terms of symptoms and jobs, across different flour-using industries. It uses the findings of a health surveillance programme in a large food organization over a five-year period. The population under surveillance consisted of 3,450 employees with exposure to ingredient dusts, of whom 400 were in flour milling, 1,650 in bread baking, 550 in cake baking and 850 in other flour-using operations. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
2
12
0
1
Order By: Relevance
“…Positive SPT to wheat grain was more prevalent among bakers compared to the control group with statistically significant difference. This is in accordance with many authors, who reported that the principal sensitizer in bread bakeries is wheat flour dust [2,3,[18][19][20][21][22]. [27] investigated pulmonary function parameters in non-smoking bakery workers and reported that the exposed group had lower forced expiratory indices than the control group.…”
Section: Disscusionsupporting
confidence: 89%
“…Positive SPT to wheat grain was more prevalent among bakers compared to the control group with statistically significant difference. This is in accordance with many authors, who reported that the principal sensitizer in bread bakeries is wheat flour dust [2,3,[18][19][20][21][22]. [27] investigated pulmonary function parameters in non-smoking bakery workers and reported that the exposed group had lower forced expiratory indices than the control group.…”
Section: Disscusionsupporting
confidence: 89%
“…These findings do not provide sufficient evidence for using exposure reduction as a management option in patients with OA and they further support the statements that reduction of exposure ''is not always effective'' [5] and that ''there is little evidence for using this approach'' [6]. The systematic review on the management of OA by BEACH et al [7] examined the outcome of symptoms [11,12,17,18,22,23,26,27,41], medications [11,12,18,23,35], FEV1 [11,12,18] and NSBHR [11,12,18] after the reduction of exposure in studies published up to 2004. The authors concluded that the majority of the studies on subjects who reduced exposure reported the following: some improvement in asthma symptoms; no clear pattern of changes in medication use; an improvement in FEV1 over time in less than half of the studies; and that there were insufficient data (improvement in one of three studies) to draw conclusions about the changes in NSBHR.…”
Section: Resultsmentioning
confidence: 97%
“…recovery, improvement and worsening) as proposed by RACHIOTIS et al [8] in their systematic review of the outcome of OA after avoidance of exposure. Six [22,23,26,27,35,41] of the 10 studies [11,12,17,18,22,23,26,27,35,41] on workers with reduced exposure in the review by BEACH et al [7] were excluded from our analysis because they did not match our pre-defined inclusion criteria. However, we analysed six studies [13-16, 19, 20] that were not included in the review of BEACH et al [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may not change or lose jobs except in the case of occupational allergy (1122). On the other hand, some allergic subjects may not take part in work with a high allergen load, e.g.…”
Section: Work Impairmentmentioning
confidence: 99%